Sustainable innovation: Economic valuation of wood waste for sustainable development at PT Wapoga Mutiara Industries - Warer, Jemmy Yohanes; Wurarah, Rully Novie; Allo, Albertus Girik; Parinussa, Silsilia Maria (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: This study describes the economic valuation of wood waste at PT Wapoga Mutiara Industries using the Market Price Approach to calculate the Total Economic Value (TEV) derived from utilising production waste. This research uses qualitative methods to explore how processed wood waste contributes economically to the company and the local community. Wood waste in industrial processes is often an underutilised asset. However, at PT Wapoga Mutiara Industries, innovative practices have turned this by-product into a significant economic opportunity. Method: This research investigated the direct use value of wood waste - mainly wood chips and sawdust – converted into local charcoal products, a resource increasingly recognized for its environmental and economic benefits. The research assessed the monthly economic impact of these waste products, measuring their market value to quantify the total benefits accruing to the local economy. Findings: The findings from this study are considerable, showing that wood chips alone contribute IDR 42,300,000 to the economy each month. Sawdust was processed in the same way, adding IDR 72,860,000 per month. Combined, these waste materials contribute a total direct use value of IDR 166,160,000 per month to the local economy, which on average provides a potential income of IDR 1,350,700 per person per month, suggesting there is significant economic potential from sustainable wood waste management practices. Conclusion: In addition, the study provides insight into the broader implications of such valuation practices, demonstrating that with the right innovations, what is often considered industrial waste can be re-evaluated as a viable economic resource. This aligns with the global shift towards more sustainable industrial processes, where waste minimisation and reuse contribute to environmental sustainability, economic resilience, and community well-being. Novelty/Originality of this study: This study presents a comprehensive analysis of the economic valuation of wood waste in the processing industry, demonstrating the significant potential of innovative waste management practices. This research opens up new perspectives on how industrial 'waste' can be transformed into valuable economic resources, supporting environmental sustainability and the well-being of local communities.